How C-Reactive Protein Structural Isoforms With Distinctive Bioactivities Affect Disease Progression - Rajab, Ibraheem M.; Hart, Peter C.; Potempa, Lawrence A. (Frontiers in Immunology, 2020)
C-reactive protein (CRP) is a widely known, hepatically synthesized protein whose blood levels change rapidly and pronouncedly in response to any tissue damaging event associated with an inflammatory response. The synthesis and secretion of CRP is stimulated by Interleukin-6, an early pleiotropic cytokine released by macrophages, endothelial, and other cells that are activated when localized normal tissue structures are compromised by trauma or disease. Serum CRP levels can change rapidly and robustly from 10-100-fold within 6-72 hours of any tissue damaging event. Elevated blood levels correlate with the onset and extent of both activated inflammation and the acute phase biochemical response to the tissue insult. Because its functional bioactivity as the prototypic acute phase reactant has eluded clear definition for decades, diagnosticians of various conditions and diseases use CRP blood levels as a simple index for ongoing inflammation. In cancer disease, which involves many different tissues, stages of disease, treatments, and responses to treatments, its interpretive diagnostic value requires a deeper understanding of the localized tissue processes and events that contribute signals which regulate protective or pathological host defense bioactivities. This report presents concepts that describe how local tissue activation events can lead to a non-proteolytic, conformational rearrangement of CRP into a unique isoform with distinctive solubility, antigenicity, binding reactivities and bioactivities from that protein widely known and measured in serum. By describing factors that control the expression, tissue localization, half-life and pro-inflammatory amplification activity of this CRP isoform, a unifying explanation for the diagnostic significance of CRP measurement in cancer disease is advanced.